2023
DOI: 10.3390/ma16144913
|View full text |Cite
|
Sign up to set email alerts
|

Stent-Graft Fabrics Incorporating a Specific Corona Ready to Fenestrate

Abstract: In situ fenestration of endovascular stent-grafts has become a mainstream bailout technique to treat complex emergent aneurysms while maintaining native anatomical visceral and aortic arch blood supplies. Fabric tearing from creating the in situ fenestration using balloon angioplasty may extend beyond the intended diameter over time. Further tearing may result from the physiologic pulsatile motion at the branching site. A resultant endoleak at the fenestrated sites in stent-grafts could ultimately lead to re-p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“… 16 , 17 Furthermore, in bench-top studies, ballooning unreinforced fenestrations to 8 mm in diameter has been shown to induce minimal fabric tearing. 18 …”
Section: Discussionmentioning
confidence: 99%
“… 16 , 17 Furthermore, in bench-top studies, ballooning unreinforced fenestrations to 8 mm in diameter has been shown to induce minimal fabric tearing. 18 …”
Section: Discussionmentioning
confidence: 99%